A study on Internet use and subjective well-being among Chinese older adults: based on CGSS (2012-2018) five-wave mixed interface survey data - Zhang, Chong; Zhang, Yong; Wang, Yan (Frontiers in Public Health, 2024)
This study is designedaimed to investigate the relationship between Internet use and subjective well-being of the older adults in China, and to analyze the mediating role of subjective social fairness in the above relationship. Based on the five-wave mixed interface survey data of China General Social Survey (CGSS) in 2012, 2013, 2015, 2017, and 2018, we selected a total of 18,458 older adults aged 60 and above, and comprehensively used ordered probit regression, propensity score matching (PSM), and Karlson-Holm-Breen (KHB) mediating effect test methods. The analysis results show that 1) Internet use is significantly positively correlated with the subjective well-being of the older adults, and the higher the frequency of use, the stronger the subjective well-being. 2) Place of residence, education, and regional factors moderated the effect of Internet use on subjective well-being. The subjective well-being effect of Internet use is significant among male older adults, as well as on urban, educated, or eastern elderly people.for urban older adults, as does schooled or eastern-central older adults. 3) Subjective social fairness Sense of social fairness plays a negative mediating role in the relationship between Internet use and subjective well-being of older adults. The findings suggest that Internet use contributes to the improvement of subjective well-being in older adults, but attenuates this effect by reducing the subjective social fairnesssense of social fairness. Future research should further consider further other factors such as the purpose, specific function, intensity of internet Internet use, etc., to gain a deeper understanding of how the internet Internet can help promote well-being.